On finite groups with Hall normally embedded Schmidt subgroups - Kniahina, V.N.; Monakhov, V.S. (Algebra and Discrete Mathematics, 2018)
A subgroup H of a finite group G is said to be Hall normally embedded in G if there is a normal subgroup N of G such that H is a Hall subgroup of N. A Schmidt group is a non-nilpotent finite group whose all proper subgroups are nilpotent. In this paper, we prove that if each Schmidt subgroup of a finite group G is Hall normally embedded in G, then the derived subgroup of G is nilpotent.